IMPLEMENTASI MODEL PEMBELAJARAN GAME BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PAI KELAS V SDN 21 KOTA PAGAR ALAM - Apla Yarida; Saepul Anwar; Achmad Faqihuddin (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
This study was motivated by the phenomenon where students often feel bored and sleepy while attending Islamic Religious Education (PAI) classes. This occurs due to monotonous teaching methods and the use of conventional teaching media. Therefore, this research aims to analyze the strategies implemented by teachers to enhance students motivation and learning outcomes. The method used was Classroom Action Research (CAR), conducted in two cycles in the fifth grade at SD Negeri 21 Kota Pagar Alam. Data were collected through observations, interviews, documentation, and pre-test and post-test assessments. Qualitative data were analyzed using the Miles and Huberman approach, while quantitative data were analyzed using a paired sample T-test with the help of SPSS and Excel 2013. The results showed a significant improvement, with 53% of students scoring above the KKM (Minimum Competency Criteria) in the first cycle, which then increased to 80% in the second cycle. The study concludes that implementing the Game-Based Learning (GBL) model using the snake and ladder game as a learning medium is effective in improving student learning outcomes in PAI subjects.